Renewable Energy - Technologies and Applications 2021
DOI: 10.5772/intechopen.91398
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics and Behaviour of Agricultural Biomass: A Short Review

Abstract: Biomass energy is one of the alternative sources of energy, which is particularly accessible in huge quantity worldwide in rural areas. Globally, solid biomass waste is the fourth as an energy resource after coil, oil and gas, which was providing approximately 14% of the world’s energy needs. The potential of biomass materials depends on feedstock quantities and their composition. The use of biomass materials as energy source provides extensive benefits as far as the environment is concerned. The agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Citing the European Forest Fire Information System (EFFIS), Horton and Palumbo (2022), reported that for the first 197 days of the year 2022 (as of 16 July 2022), almost 346,000 hectares of land were burned by wild fires in the European Union. Other authors have reported on the combustion characteristics of different types of biomass (Haykiri-Acma, 2003;Demirbas, 2004;Hao, 2020;Suman et al, 2021), and on the emission factors for biomass and fossil fuel-fired stoves (Gaegauf et al, 2001;Bhattacharya et al, 2002;Johansson, 2002;Edwards et al, 2003;Boman et al, 2004;Sippula et al, 2007;Bäfver et al, 2011;Njenga et al, 2014;Obaidullah and De Ruyck, 2021).…”
Section: Air Pollutionmentioning
confidence: 99%
“…Citing the European Forest Fire Information System (EFFIS), Horton and Palumbo (2022), reported that for the first 197 days of the year 2022 (as of 16 July 2022), almost 346,000 hectares of land were burned by wild fires in the European Union. Other authors have reported on the combustion characteristics of different types of biomass (Haykiri-Acma, 2003;Demirbas, 2004;Hao, 2020;Suman et al, 2021), and on the emission factors for biomass and fossil fuel-fired stoves (Gaegauf et al, 2001;Bhattacharya et al, 2002;Johansson, 2002;Edwards et al, 2003;Boman et al, 2004;Sippula et al, 2007;Bäfver et al, 2011;Njenga et al, 2014;Obaidullah and De Ruyck, 2021).…”
Section: Air Pollutionmentioning
confidence: 99%
“…The potential for using biomass materials depends on the availability of raw materials and their composition [15]. Moreover, physicochemical and structural analyses of agricultural biomass can vary significantly, depending on the type of raw material used [16,17]. To achieve optimal integration, it is crucial to classify biomass waste based on the available bioprocesses [18].The cultivation of specialized energy crops significantly contributes to environmental burdens due to water consumption and the use of chemical fertilizers.…”
Section: Introductionmentioning
confidence: 99%